Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2009
DOI: 10.1145/1518701.1519012
|View full text |Cite
|
Sign up to set email alerts
|

A mobile voice communication system in medical setting

Abstract: Hospital work coordination and collaboration often requires mobility for acquiring proper information and resources. In turn, the spatial distribution and the mobility of clinicians can curtail the opportunities for effective communications making collaboration difficult. In this situation, a mobile hands-free voice communication system, Vocera, was introduced to enhance communication. It supports quick and impromptu conversations among coworkers for work coordination and collaboration anytime and anywhere. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Collaborative healthcare practices often require that workers have timely access to people, information, and resources (Bardram and Bossen 2005 (Hanada et al 2006;Tang and Carpendale 2009a). In particular, such devices allow clinicians to continue with a current task while communicating with team members about other patients or tasks, improving the efficiency and the quality of patient care (Tang and Carpendale 2009a).…”
Section: Technology For Supporting Distributed Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Collaborative healthcare practices often require that workers have timely access to people, information, and resources (Bardram and Bossen 2005 (Hanada et al 2006;Tang and Carpendale 2009a). In particular, such devices allow clinicians to continue with a current task while communicating with team members about other patients or tasks, improving the efficiency and the quality of patient care (Tang and Carpendale 2009a).…”
Section: Technology For Supporting Distributed Communicationmentioning
confidence: 99%
“…In particular, such devices allow clinicians to continue with a current task while communicating with team members about other patients or tasks, improving the efficiency and the quality of patient care (Tang and Carpendale 2009a). Similarly, Richardson and Ash (2008) found that the use of hands-free communication devices in clinical settings provided clinicians with better communication access and also better control over the information they could access.…”
Section: Technology For Supporting Distributed Communicationmentioning
confidence: 99%
“…In the near future (already in some hospitals), scheduling information will be distributed to handheld devices (e.g., [12], [14], [29]). Some of the designs we have seen obviate group discussions around the schedule.…”
Section: Discussionmentioning
confidence: 99%
“…To support these work processes, hospital staff rely on a variety of artifacts, including paper schedules, electronic records, schedule boards, and mobile devices (e.g., [29], [33], [21]). …”
Section: Figurementioning
confidence: 99%
“…In recent years, the literature has abounded with examples of partially successful implementations that result in resistance to adoption, increased patient safety concerns, and changed workflows in unanticipated ways [1,2]. The introduction of technology into the healthcare clinical environment has been shown to change clinical patient care in ways that prevent communication of important psycho-social patient parameters [2], to create conditions predisposing to medical errors [1], to desensitize clinicians to alerts [3], or to change the nature of collaborative work such as the task of handover [4]. The most common and overt consequences are incurred investment overhead of increased demand for training, repeated rollouts, costly inservices, as well as workarounds devised by end-users, which undermine the benefits of the implemented technology.…”
Section: Introductionmentioning
confidence: 99%